Risk assessment of preeclampsia - Zuzanna Tomczewska; Aleksandra Rykucka; Natalia Zozula; Marcin Wąs; Justyna Kiełbasa; Agata Kowalczyk; Katarzyna Bil; Iga Ślesicka; Aleksandra Latała; Magda Przestrzelska (Nicolaus Copernicus University in Toruń, 2024)
Introduction and purpose: Preeclampsia (PE) is a complication during pregnancy characterized by high blood pressure (≥140/90 mmHg) and signs of organ involvement appearing after 20 weeks' of gestation. Various factors are known to increase the risk of this condition as well as clinical factors. The pathogenesis of the disease is complex and not fully understood. State of Knowledge: The main roles play two angiogenic factors: soluble fms-like tyrosine kinase 1 (sFlt-1), which is an antiangiogenic protein, and placental growth factor (PlGF), which is a pro-angiogenic protein. Elevated sFlt-1 and reduced PlGF levels in the mother's blood can predict the future development of preeclampsia during pregnancy. The imbalance between these two angiogenic biomarkers indicates de new-onset preeclampsia, distinct from chronic hypertension. Both MAP and UTA-PI are essential components of first-trimester screening protocols, which, combined with maternal history and other biochemical markers, allow for accurate preeclampsia risk assessment and early intervention to improve maternal and fetal outcomes. Conclusions: Preeclampsia is a major cause of maternal and perinatal morbidity and mortality. The integration of multiple biomarkers, such as PlGF and sFlt-1, along with advanced analytical techniques, enhances early detection and accurate risk stratification, improving maternal and fetal outcomes. Aspirin prophylaxis before 16 weeks' gestation has been shown to reduce the risk of preeclampsia.